Cardiovascular Biomarkers and Calculated Cardiovascular Risk in Orally Treated Type 2 Diabetes Patients: Is There a Link? - Markova, Aleksandra; Boyanov, Mihail; Bakalov, Deniz; Kundurdjiev, Atanas; Tsakova, Adelina (Hormone and Metabolic Research, 2020)
The aim of the study was to test the correlation of serum levels of asymmetric dimethylarginine (ADMA), endothelin 1 (ET-1), N-terminal brain natriuretic pro-peptide (NT-proBNP), and placental growth factor (PIGF-1) with estimated cardiovascular (CV) risk. The study group was composed of 102 women and 67 men with type 2 diabetes, having their glycemic and metabolic parameters assessed. All were on oral antidiabetic drugs. Serum levels of NT-proBNP and PIGF-1 were measured by electro-hemi-luminescence on an Elecsys 2010 analyzer. Enzymatic immunoassays were used for ADMA and ET-1. The Framingham Risk Score (FRS), the UKPDS 2.0 and the ADVANCE risk engines were used to calculate cardiovascular risks while statistical analysis was performed on SPSS. Levels of PIGF-1 showed no correlation with the calculated CV risks. The same was true for ADMA, except for a weak correlation with the UKPDS-based 10-year risk for stroke (Pearsons’s R=0.167, p=0.039). Plasma levels of ET-1 were correlated with the UKPDS-based 10-year risk for stroke (R=0.184, p=0.032) and fatal stroke (R=0.215, p=0.012) only. NT-proBNP was significantly correlated with all CV risk calculations: ADVANCE-based 4-yr risk (Spearman’s Rho=0.521, p<0.001); UKPDS-based 10-year risk for: CHD (Rho=0.209, p=0.01), fatal CHD (Rho=0.282, p<0.001), stroke (Rho=0.482, p<0.001), fatal stroke (Rho=0.505, p<0.001); and 10-year FRS risk (Rho=0.246, p=0.002). In conclusion, ADMA and PIGF-1 did not seem useful in stratifying CV risk while ET-1 is linked to the risk of stroke, and NT-proBNP to all CV risk estimations.
Keywords: NT-proBNP; ADMA; endothelin-1; risk calculators; correlations; PIGF-1